Representation of Stuttering in the United Sates Newspaper Media. Issue 4 (1st October 2020) - Azios, Michael; Irani, Farzan; Rutland, Brittany; Ratinaud, Pierre; Manchaiah, Vinaya
Abstract: The understanding of how stuttering is portrayed in the newspaper media has largely been ignored but plays a role in public perception of stuttering. A text pattern analysis, cross-sectional study was conducted based upon analyses of publicly available data. The text corpus were generated from the U.S. newspaper media during 1980–2018 (downloaded from the database U.S. Major Dailies by ProQuest). The text corpuses were analyzed using the Iramuteq software using the cluster analysis and Chi square tests. The newspaper data set had 970 texts (i.e., articles in the main corpus). The cluster analysis of the main corpus resulted in six clusters, which were named as: (1) music (2) sports (3) politics and economy (4) speech (5) cinema, and (6) general. The sub-corpus which was built based on aspects related to speech (i.e., cluster 4 in main corpus analysis) had 539 texts, which had at least one segment in sub-corpus. The cluster analysis of sub corpus resulted in four clusters, which were named as: (1) education and social support (2) personal aspects (3) aspects related to speech and (4) research and development. Time series analysis of clusters indicated a change in the pattern of information presented in newspaper media during 1980–2018. The study shows that stuttering has been presented in the media while discussing various elements including sports, arts and politics and economy, and speech. The aspects related to speech found media focuses on various elements including personal aspects, providing education and support, and providing new insights into research and development